Effects of Killing Liquids on the Larval Length of Forensically Important Lucilia sericata - Açıkgöz, Halide Nihal; Açıkgöz, Ali (The Bulletin of Legal Medicine, 2018)
Objective: Forensic entomological practices rely upon accurate larval identification and measurement of larval length, for the estimation of post-mortem intervals. The methods used for killing larvae may affect the length of larvae. In the autopsy hall, corpses which are contain entomological remains have been washed with grape vinegar. Besides, while collecting and killing the larvae on corpses, crime scene teams use ethanol 70% because it is practical. The aim of this study was to determine which of hot water (90°C), cold vinegar and cold ethanol 96% method, preserved the best the length of larvae. Materials and Methods: To achieve this aim, third instar larvae which are reared on 200 g of veal meat were killed using hot water, cold vinegar and cold ethanol. Before killing and after killing the maggots, their length was measured. To determine the difference between the groups to be compared ANOVA test, to reliability and validity analyses Kruskal-Wallis and whether there was any difference between the groups were made with Tukey’s Honestly Significant Difference (Tukey’s HSD) Results and Conclusion: Hot water was found to preserve the length of the larvae more accurately than cold vinegar and ethanol. Forensic medicine experts and crime scene teams should kill the larvae collected from a corpse for entomological examination using hot water, dry them in paper towels and preserve them in 96% ethanol and then send them to a forensic entomologist.